2017
DOI: 10.1093/mnras/stx2667
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of mergers on the angular momentum of simulated galaxies

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
113
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 100 publications
(163 reference statements)
15
113
1
1
Order By: Relevance
“…As has been shown in previous work (e.g. Lotz et al 2010;Naab et al 2014;Lagos et al 2018;Martin et al 2018), gas-rich mergers will 'spin up' merger remnants, as the gas creates a new rotationally-supported stellar component. As shown graphically in Figure 2 (top row, left-hand column), these gas-rich recent mergers produce an uptick in V /σ, that moves the system from the spheroid to the disc regime.…”
Section: The Dominant Channel Of Massive Disc Formation: Disc Rejuvensupporting
confidence: 58%
“…As has been shown in previous work (e.g. Lotz et al 2010;Naab et al 2014;Lagos et al 2018;Martin et al 2018), gas-rich mergers will 'spin up' merger remnants, as the gas creates a new rotationally-supported stellar component. As shown graphically in Figure 2 (top row, left-hand column), these gas-rich recent mergers produce an uptick in V /σ, that moves the system from the spheroid to the disc regime.…”
Section: The Dominant Channel Of Massive Disc Formation: Disc Rejuvensupporting
confidence: 58%
“…Darg et al (2010) studied merging galaxies with tidal features identified through the Galaxy Zoo project and concluded that the effects of mergers on spiral galaxies were much more dramatic (eroding their gas and angular momentum supplies and strongly enhancing their SFRs), so disturbed spiral galaxies were more easily observable than disturbed ellipticals. This result may also reflect the fact that modest gas fractions are expected to lead to more spheroidal remnant morphologies (Naab et al 2006;Duc & Renaud 2013), while gas-rich mergers should yield diskdominated remnants (Lotz et al 2008;Hopkins et al 2009;Lagos et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…with comparable values of xi) have much stronger ramifications than minor ones in terms of restructuring the dark matter (Ludlow et al 2012;Klypin et al 2016) and transforming the dynamics and kinematics of galaxies (e.g. Conselice 2014; Lagos et al 2018a). Translated to our problem, this means that more similar values {xi} should lead to higher values of s than more diverse sets.…”
Section: Self-similar Treesmentioning
confidence: 99%
“…In the CDM framework of structure formation, the stellar content of galaxies grows via two processes: internally by gas cooling and star formation in the host halo; and externally by accretion of other galaxies (Guo & White 2008;Zolotov et al 2009;Oser et al 2010;Pillepich et al 2015). The balance between these two processes affects a number of key observables, such as the morphology (Kormendy et al 2009), the amount of kinematic support (Lagos et al 2018a) and the structure of the stellar halo (Helmi et al 2018). Since the coalescence of galaxies is normally triggered by an earlier merger of their haloes, the hierarchical assembly of haloes is pivotal to understanding the evolution of galaxies (Toomre & Toomre 1972;White & Frenk 1991;Conselice 2014).…”
Section: Introductionmentioning
confidence: 99%